News platformization: an analysis of the levels of platformized presence of portuguese news media Abstract. - de Mattos, Fabrício Santos (2023)
News platformization is a global phenomenon characterized by the growing centrality of social media and search engines in news distribution, thus transforming news media into producers of content that complement these digital ecosystems. In this context, the research used a quantitative analysis based on the intersection of media mapping studies and platformization studies to understand how Portuguese news media position themselves on platforms. Three steps were taken: news media codification and mapping, classification of their different levels of presence, and characterization and comparison between such levels. The classification was conducted with a combination of hierarchical and non-hierarchical cluster analyses, identifying three levels of platform presence—low, medium, and high—on Facebook, Instagram, Twitter, and YouTube. It is concluded that the reach and the medium of origin are important factors, but this relationship is not direct since the integration of Portuguese news media also depends on the adaptation to the logic of digital platforms and how they show their contents, according to the potential and audiences of each communication environment.